Obesity, Insulin Resistance, Hypertension and Sleep in the Child - Kohyama, Jun (International Journal of Child Health and Nutrition, 2012)
Sleep loss produces various insults on human health. The current mini-review introduces recent evidence on the relationship among sleep loss, obesity, insulin resistance, hypertension, and sleep apnea with paying special attention to children. Ten relationships were explained; 1. Sleep loss induces obesity. 2. Obesity induces sleep apnea. 3. Obesity induces insulin resistance. 4. Obesity induces hypertension. 5. Sleep loss induces insulin resistance. 6. Sleep loss induces hypertension. 7. Sleep apnea with obesity induces insulin resistance. 8. Sleep apnea with obesity induces hypertension. 9. Sleep apnea without obesity induces insulin resistance. 10. Sleep apnea without obesity induces hypertension. To secure child health, the need for paying attention to sleep was emphasized.